Advances in the Understanding of Reactive Oxygen Species-Dependent Regulation on Seed Dormancy, Germination, and Deterioration in Crops - Li, Wenjun; Niu, Yongzhi; Zheng, Yunye; Wang, Zhoufei (Frontiers in Plant Science, 2022)
Reactive oxygen species (ROS) play an essential role in the regulation of seed dormancy, germination, and deterioration in plants. The low level of ROS as signaling particles promotes dormancy release and triggers seed germination. Excessive ROS accumulation causes seed deterioration during seed storage. Maintaining ROS homeostasis plays a central role in the regulation of seed dormancy, germination, and deterioration in crops. This study highlights the current advances in the regulation of ROS homeostasis in dry and hydrated seeds of crops. The research progress in the crosstalk between ROS and hormones involved in the regulation of seed dormancy and germination in crops is mainly summarized. The current understandings of ROS-induced seed deterioration are reviewed. These understandings of ROS-dependent regulation on seed dormancy, germination, and deterioration contribute to the improvement of seed quality of crops in the future.